2015
DOI: 10.1007/s00120-015-3856-6
|View full text |Cite
|
Sign up to set email alerts
|

Volkswirtschaftliche Bedeutung der postoperativen Harninkontinenz

Abstract: In the 22,160 patients treated in Germany for prostate cancer by prostatectomy, the costs for direct and indirect sequelae as the result of postoperative urinary incontinence are estimated to be 71.8 million €. This greatly exceeds the costs of 69.8 million € for the operation itself. This additional economic burden can, however, be decisively influenced by using a surgical technique that preserves the integrity of the urethral sphincter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
0
1
Order By: Relevance
“…25 Lent et al 26 showed that the costs of the direct and indirect consequences of the PPI in Germany in 2013 were estimated at 71.8 million €, which was more than the costs of the RP itself, which amounted to 69.8 million €. 26 Therefore, it is important to reduce the possibility of PPI to a minimum. It has already been shown that preoperative profilometric data can be a significant indicator of continence recovery after RP.…”
Section: Resultsmentioning
confidence: 99%
“…25 Lent et al 26 showed that the costs of the direct and indirect consequences of the PPI in Germany in 2013 were estimated at 71.8 million €, which was more than the costs of the RP itself, which amounted to 69.8 million €. 26 Therefore, it is important to reduce the possibility of PPI to a minimum. It has already been shown that preoperative profilometric data can be a significant indicator of continence recovery after RP.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies, not included in the review have examined costs in patients with these conditions. For example, one publication (excluded from the current review as is was not published in English) estimated that in Germany the direct and indirect costs associated with urinary incontinence following prostatectomy are approximately EUR 71.8 million [73]. Similarly, figures from the UK estimate that on a per patient level, the annual cost of erectile dysfunction is GBP 335 [74].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary incontinence has a significant economic cost. The economic burden of urinary incontinence following radical prostatectomy is comparable to that of the instigating surgery (Lent 2015). The estimated economic burden of managing urinary incontinence in men in the USA was USD 18.8 billion (USD 18,800 million, USD 1998/1999), with a trend showing a rapid increase for men above the age of 65 years (Stothers 2005).…”
Section: Description Of the Conditionmentioning
confidence: 99%